Asiatic acid nano-structure lipid carrier and soluble microneedle drug delivery system
By preparing asiatic acid nanostructured lipid carriers and soluble microneedle drug delivery systems, the problems of poor water solubility and poor absorption of asiatic acid in scar treatment were solved, thereby improving the drug absorption efficiency and therapeutic effect.
Patent Information
- Application Number
- CN202511361258.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2025-10-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Asiatic acid has poor water solubility and poor absorption when used to treat scars, resulting in unsatisfactory treatment effects.
Asiatic acid was prepared into a nanostructured lipid carrier and combined with a soluble microneedle drug delivery system. The microneedles puncture the thickened scar tissue to promote transdermal drug absorption, and the sustained-release properties of the nanostructured lipid carrier were used to reduce adverse reactions.
It improves the absorption efficiency of asiatic acid, increases transdermal penetration, reduces adverse drug reactions, and achieves a synergistic and toxicity-reducing therapeutic effect.
Smart Images

Figure CN120837660A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, specifically to a asiatic acid nanostructure lipid carrier and a soluble microneedle drug delivery system. Background Technology
[0002] Scars, also known as "scarring," refer to the general term for changes in appearance and histopathology of normal skin tissue caused by external trauma. If the damage reaches the dermis, it can lead to pathological scars such as hypertrophic scars and keloids, which are characterized by a high recurrence rate and difficulty in treatment. When hypertrophic scars occur in areas such as joints, around the eyes, and around the lips, they can cause varying degrees of functional impairment, such as limited joint flexion, extension, and rotation, and restricted eye or mouth opening, causing considerable inconvenience to the patient's life. The appearance of scars not only affects the local aesthetics of tissues and organs but also creates significant psychological stress for patients. The treatment of scars has always been a major challenge in clinical practice.
[0003] Currently, numerous treatment methods exist for scars, with surgical excision being the primary approach, supplemented by occlusive dressings, cryotherapy, radiation and laser therapy, and medication. However, issues such as recurrence after surgery, infection risks associated with occlusive dressings, inherent risks with radiation therapy, and long healing times with laser therapy remain unresolved. Drug treatments primarily involve local injections of corticosteroids, steroids, or 5-fluorouracil, as well as topical applications of silicone gels and Centella asiatica cream. However, clinical results indicate that these treatments are often ineffective and expensive. Repeated local injections can cause significant pain, and long-term use of steroids carries substantial side effects such as obesity and edema. Regardless of whether these treatments are used alone or in combination, their efficacy remains unsatisfactory, and their safety, effectiveness, and stability are difficult to guarantee. Centella asiatica acid, an extract of Centella asiatica, offers advantages such as easy extraction, hormone-free composition, and relatively high safety. It shows good therapeutic effects on skin ulcers, scars, keloids, and localized scleroderma, demonstrating promising market prospects for inhibiting scar hyperplasia. However, traditional asiatic acid preparations have poor water solubility, poor absorption, rapid elimination in the body, and low blood drug levels, which greatly restricts their application.
[0004] The main reason for the unsatisfactory effect of asiatic acid in treating scars lies in the special structure of scar tissue and the limitations of the drug itself, such as poor water solubility and poor absorption. To address this issue, this invention tackles it from two aspects: First, by changing the dosage form, the drug is prepared as a nanostructured lipid carrier to improve absorption. Second, a microneedle nanocarrier system is used for novel local transdermal delivery, piercing the thickened scar tissue to overcome the low drug absorption efficiency caused by scarring. Summary of the Invention
[0005] To address the technical problem of unsatisfactory therapeutic effects of asiatic acid in treating scars due to the unique structure of scar tissue and the limitations of poor water solubility and transdermal absorption of asiatic acid itself, this invention provides an asiatic acid nanostructured lipid carrier and a soluble microneedle drug delivery system. By designing and optimizing the dosage form of asiatic acid, the drug is prepared as a nanostructured lipid carrier to improve absorption and maximize its efficacy. A soluble microneedle drug delivery system based on soluble microneedles is designed. By combining microneedles and the asiatic acid nanostructured lipid carrier, a novel local transdermal delivery method is used to puncture thickened scar tissue, promoting the transdermal absorption of poorly soluble Chinese medicine components. This fully leverages the physicochemical permeation-enhancing advantages of the microneedle-nanostructured lipid carrier, increasing transdermal penetration and overcoming the low drug absorption efficiency caused by scarring. Furthermore, the sustained-release properties of the nanostructured lipid carrier reduce adverse drug reactions, thereby achieving a synergistic effect and reduced toxicity.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a process for preparing a asiatic acid nanostructured lipid carrier, comprising the following steps: S1. Weigh 4-6 parts by weight of asiatic acid, 34-38 parts by weight of solid lipids, and 7-10 parts by weight of liquid lipids, and dissolve them in 4-6 mL of anhydrous ethanol. S2. At 65-75℃, add the above mixed solution to 50mL of water at the same temperature and stir until homogeneous to obtain a cloudy liquid with an opalescent appearance. S3. After cooling the turbid liquid to room temperature, adjust the pH with hydrochloric acid. The precipitate obtained by centrifugation is washed with a small amount of deionized water, centrifuged again, and the upper liquid is discarded to obtain the asiatic acid nanostructure lipid carrier precipitate. S4. The asiatic acid nanostructured lipid carrier precipitate was freeze-dried to obtain asiatic acid nanostructured lipid carrier freeze-dried powder.
[0007] Furthermore, in step S1, the solid lipid is glyceryl monostearate and the liquid lipid is oleic acid.
[0008] Further, in step S1, the amount of asiatic acid is 5 parts by weight, the amount of solid lipid is 36 parts by weight, the amount of liquid lipid is 9 parts by weight, and the amount of anhydrous ethanol is 5 mL.
[0009] Furthermore, in step S2, the heating temperature of the mixed solution is 70°C.
[0010] The present invention also provides a asiatic acid nanostructured lipid carrier, which is prepared by the above-described preparation process.
[0011] The present invention also provides an application of the above-mentioned asiatic acid nanostructured lipid carrier, wherein the asiatic acid nanostructured lipid carrier is used as a drug for treating scar tissue.
[0012] The present invention also provides a soluble microneedle drug delivery system, wherein the soluble microneedle drug delivery system is a microneedle patch, the microneedle patch is composed of a microneedle tip and a patch, and the above-mentioned asiatic acid nanostructure lipid carrier is loaded into the microneedle tip and / or the patch.
[0013] The needle tip and patch were manufactured using a two-step process, employing a "sandwich method" to load AA-NLC lyophilized powder into the middle layer of both the needle tip and patch. The preparation process of the AA-NLC soluble microneedle patch is as follows: The microneedle fabrication process employs a reverse centrifugation method, primarily involving two steps. The first step is the preparation of the microneedle tips. The best-performing microneedle tip material, selected through screening, is spread onto a microneedle negative mold (placed in a six-well plate). The mold is then centrifuged at 3500 rpm for 10 minutes at 15°C using a low-temperature plate ultracentrifuge. After centrifugation, the position of the six-well plate is reversed, and centrifugation continues for another 10 minutes. This process is repeated once to allow the microneedle tip material to enter the voids in the negative mold needle tip under centrifugal force. After centrifugation, excess polymer microneedle material is scraped off with a flat-headed spatula, and the mold is placed in a vacuum drying oven for 12 hours. Under gravity, soluble microneedle tips with cavities are obtained. The second step involves loading the prepared microneedle tip negative mold with AA-NLC lyophilized powder using a dry powder loading method. After drug loading, the selected microneedle patch backing material is filled into the negative mold. The microneedles were flattened by centrifugation at a decreasing speed at 15℃. Finally, the microneedles were dried at room temperature for 24-48 hours to observe their formation. After drying, they were carefully removed with pointed tweezers to obtain the AA-NLC microneedle patch.
[0014] Furthermore, the matrix material of the microneedle patch is sodium chondroitin sulfate.
[0015] Further, the chondroitin sulfate sodium mass fraction is 35-45%. Preferably, the chondroitin sulfate sodium mass fraction is 40%.
[0016] Furthermore, the chondroitin sulfate sodium gel material was spread throughout the prepared microneedle negative mold and placed in a vacuum drying oven. Under negative pressure, the chondroitin sulfate sodium gel material filled the cavities of the microneedle negative mold. The microneedle mold was then placed in a refrigerator for pre-freezing and subsequently placed in a freeze dryer for freeze drying. After drying, the complete microneedle patch was removed with pointed tweezers.
[0017] Compared with the prior art, the present invention has the following beneficial effects: Asiatic acid (AA), the main component of asiaticoside, is a ursane-type pentacyclic triterpene acid that has attracted much attention due to its broad pharmacological activity. However, there are two issues that urgently need to be addressed regarding the application of asiatic acid in scar treatment. One issue is the poor water solubility and low bioavailability of asiatic acid. To address this problem, this invention constructs a nanostructured lipid carrier of asiatic acid. Nanostructured lipid carriers (NLCs) have a solubilizing effect on poorly soluble drugs, increasing the local concentration of the drug. Specifically, this invention prepares asiatic acid nanostructured lipid carriers (AA-NLCs) using solvent diffusion technology. The effects of different ethanol dosages and temperatures on the nanostructured lipid carriers were investigated using average particle size and surface potential as evaluation indicators. The formulation process of asiatic acid nanostructured lipid carriers (AA-NLCs) was preliminarily determined. The asiatic acid nanostructured lipid carriers (AA-NLCs) were characterized by drug loading, encapsulation efficiency, in vitro release characteristics, and microstructure. Finally, the optimal formulation and ratio were determined, using glyceryl monostearate as the solid lipid, oleic acid as the liquid lipid, ethanol as the solvent, and water as the aqueous phase. The preparation temperature was controlled at 70℃. The asiatic acid nanostructured lipid carriers (AA-NLCs) were successfully prepared using solvent diffusion technology. The AA-NLC nanoparticles have a particle size of 381.9±2.6 nm and a potential of -37.8±1.8 mV; the drug encapsulation efficiency is 77.9±4.8%; the drug loading is 8.8±0.7%; AA-NLC exhibits significant sustained-release characteristics, releasing approximately 85% in 5 days.
[0018] Another issue is the dysfunction of the stratum corneum in the scar area, resulting in low drug penetration. This invention selects soluble microneedles as a carrier to deliver the drug into the scar. A force of 0-0.436N is applied vertically to the soluble microneedles prepared with the optimal formulation and process. When the force on a single soluble microneedle reaches 0.006N (greater than the force required to penetrate the skin, 3.596 × 10⁻⁶), the drug is delivered effectively. -4The microneedle tip remained intact, without significant deformation or bending. Under a vertical force of 0.013N, the microneedle began to bend and deform. When a vertical force of 0.125N was applied to a single needle, the tip of the microneedle slightly bent and deformed, but without breakage, and the compressive force was less than 15%. This deformation test was conducted on a hard surface, which exaggerates the deformation of soluble microneedles compared to testing in soft tissue. Therefore, chondroitin sulfate lyophilized soluble microneedles have sufficient mechanical strength to penetrate the skin. This invention establishes a novel intradermal drug delivery system using a soluble microneedle array, providing a treatment method that can uniformly deliver drugs (centella asiatica nanostructured lipid carriers) to scar tissue. Based on the novel transdermal delivery method of microneedle nanolipocarriers, it can promote the transdermal absorption of poorly soluble traditional Chinese medicine components, fully utilize the physicochemical permeation-enhancing advantages of microneedles-nanostructured lipid carriers, increase transdermal penetration, and utilize the sustained-release properties of nanostructured lipid carriers to reduce adverse drug reactions, thereby achieving synergistic effects and reduced toxicity. Attached Figure Description
[0019] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0020] Figure 1 The particle size distribution diagram of AA-NLC prepared in Example 5; Figure 2 Transmission electron microscopy (TEM) images of AA-NLC prepared in Example 5; Figure 3 The XRD patterns of the samples are shown. A, B, and C are the XRD patterns of asiatic acid (AA) monomer powder, blank NLC, and AA-NLC, respectively. Figure 4 The in vitro release curve of AA-NLC prepared in Example 5; Figure 5 The images show the physical appearance and scanning electron microscope (SEM) image of the microneedle patch. Figure 6 The microneedle hardness test curve; Figure 7 The morphological changes and compressibility of microneedles under different stresses; Figure 8 For the water solubility test of lyophilized microneedles (0s→10s→20s→40s→60s→90s continuous micrographs). Figure 9 This is a diagram of microneedle ex vivo skin puncture. Figure 10 Images showing the healing process of skin wounds punctured by microneedles (0 min → 4 min → 8 min → 12 min → 16 min → 20 min → 24 min → 28 min, taken continuously). Detailed Implementation
[0021] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0022] I. Construction and Physicochemical Properties of Asiatic Acid Nanostructured Lipid Carrier (AA-NLC) This experiment used solvent diffusion technology to prepare asiatic acid nanostructured lipid carriers (AA-NLC). The effects of different ethanol dosages and temperatures on AA-NLC were investigated using average particle size and surface potential as evaluation indicators. The formulation and process of AA-NLC were preliminarily determined. AA-NLC was characterized by drug loading, encapsulation efficiency, in vitro release characteristics, and microstructure.
[0023] 1.1 Prepare a 0.1 wt% poloxamer aqueous solution. Weigh 0.1g of poloxamer, dissolve it in 100mL of water, and shake well to obtain the product.
[0024] 1.2 Preparation of AA-NLC Dispersion AA-NLC was prepared by solvent diffusion method using glyceryl monostearate as the solid lipid and oleic acid as the liquid lipid.
[0025] The specific preparation process is as follows: S1. Accurately weigh 5 mg of asiatic acid, 36 mg of glyceryl monostearate and 9 mg of oleic acid and dissolve them in a certain volume of anhydrous ethanol. S2. The mixed solution was added to 50 mL of water at the same temperature under certain temperature conditions, and mechanically stirred at 400 rpm for 5 min to obtain a cloudy liquid with an opalescent appearance. S3. After cooling the turbid liquid to room temperature, adjust the pH with hydrochloric acid, centrifuge to precipitate, wash the precipitate with a small amount of deionized water, centrifuge again, discard the supernatant, and obtain AA-NLC precipitate. S4. The resulting precipitate was dispersed in 50 mL of 0.1 wt% poloxamer aqueous solution to obtain AA-NLC dispersion.
[0026] Preparation of AA-NLC lyophilized powder: The asiatic acid nanostructured lipid carrier precipitate was freeze-dried to obtain asiatic acid nanostructured lipid carrier lyophilized powder.
[0027] The freeze-drying conditions were: pre-freezing at -45°C for 6 hours; vacuum drying at -40°C for 12 hours; vacuum drying at -10°C for 6 hours; and vacuum drying at 25°C for 6 hours to obtain freeze-dried nanoparticle powder.
[0028] 1.3 Experimental Setting of Preparation Process Parameters for Single-Factor Screening The size and dispersibility of nanoparticles have a significant impact on their quality. To prepare AA-NLC microparticles with moderate size, narrow particle size distribution, and high dispersibility, the effects of two key factors—the water bath temperature in step S2 and the amount of ethanol used in step S1—on the preparation of AA-NLC were investigated, using particle size distribution and surface charge as evaluation indicators.
[0029] (1) The effect of temperature: In Examples 1-3, the amount of anhydrous ethanol used in step S1 in each example is 5 mL, and the water bath temperature in step S2 is 0℃, 35℃, and 70℃, respectively.
[0030] (2) Effect of ethanol dosage: In Examples 4-6, the water bath temperature in step S2 is set to 70°C, and the amount of anhydrous ethanol used in step S1 is 2 mL, 5 mL, and 8 mL, respectively.
[0031] (3) The physicochemical properties of the AA-NLC prepared in Examples 1-3 and Examples 4-6 were tested: Determination of particle size and zeta potential The AA-NLC dispersion was diluted 40 times with 0.1wt% poloxamer aqueous solution and the particle size distribution was measured using a particle size potential analyzer.
[0032] Nanoparticle surface morphology observation Take the AA-NLC dispersion, drop it onto a copper grid, and perform negative staining with 2wt% phosphotungstic acid. Observe the surface structure under a transmission electron microscope.
[0033] XRD analysis of microstructure Accurately weigh appropriate amounts of AA-NLC lyophilized powder, blank NLC lyophilized powder, and AA monomer, and evaluate the microstructure of AA-NLC by powder X-ray diffraction (XRD). The instrument used Cu Kα radiation, with a scanning angle 2θ of 5-50°, a step size of 0.0167°, and an interval of 10 s.
[0034] Encapsulation efficiency and drug loading determination AA is almost insoluble in water, and its saturated solubility in a 30% ethanol aqueous solution at room temperature is 16.7 μg·mL⁻¹, while lipid materials such as glyceryl monostearate are almost insoluble in this solution at room temperature.
[0035] Therefore, this experiment used 30% ethanol solution as solvent and determined the encapsulation rate and drug loading by ultrasonically dissolving the unencapsulated free drug in the nanoparticles.
[0036] Here are the steps: Accurately weigh approximately 40 mg of lyophilized nanoparticle powder, add 10 mL of 30% ethanol solution, and ultrasonically disperse (working for 2 seconds, stopping for 3 seconds, power at 400 W, total working time 2 minutes) to obtain a dispersion. Take an appropriate amount of the dispersion, centrifuge at 20,000 rpm for 5 min, accurately transfer 1 mL of the supernatant to a 2 mL volumetric flask, dilute with anhydrous ethanol, filter through a 0.45 μm filter membrane, determine the amount of free drug in the filtrate by HPLC and calculate the amount of free drug. Accurately transfer 1 mL of the dispersion into a 10 mL volumetric flask, dilute with anhydrous ethanol, incubate in a 70°C water bath for 30 min, cool to room temperature, add ethanol to the mark, filter through a 0.45 μm filter membrane, determine the drug concentration in the filtrate by HPLC and calculate the total drug amount.
[0037] The formulas for calculating encapsulation efficiency and drug loading are as follows: Encapsulation efficiency = (Drug content in nanoparticles - Free drug content) / Dosage amount × 100%; Drug loading = (Drug content in nanoparticles − Free drug content) / Total weight of nanoparticles (lyophilized powder) × 100%.
[0038] In vitro release assay of asiatic acid nanostructured lipid carrier Take an appropriate amount of AA-NLC dispersion (approximately 0.6 mg of drug) and place it in a dialysis bag (molecular weight cutoff 3500, pretreated before use). Place the dialysis bag in a release flask (3.5 cm in diameter, bag submerged) containing 18 mL of PBS (pH 7.4, containing 1 wt% SDS) release medium and shake at 37°C and 100 rpm. Collect all release medium at 0.5, 1, 2, 4, 6, 8, 10, 24, 48, and 96 h, and immediately replenish with the same volume of fresh release medium. Determine the drug content in the sample by HPLC. Prepare a 0.5 mg / mL methanol solution of AA to investigate the dialysis bag's inhibitory effect on AA.
[0039] 1.4 Results of Formula Process Optimization Table 1 shows the effect of different amounts of anhydrous ethanol on AA-NLC in Examples 4-6, and Table 2 shows the effect of different water bath temperatures on AA-NLC in Examples 1-3. Three sets of repeated experiments were set up for each example. After screening, it was finally determined that the water bath temperature in preparation step S2 is preferably 70℃, and the amount of ethanol in step S1 is preferably 5mL.
[0040] Table 1 Anhydrous ethanol volume (mL) Particle size (nm) Surface charge (mV) 2 424.0±10.5 -37.6±0.6 5 381.9±2.6 -37.8±1.8 8 454.4±19.9 -35.5±4.0 Table 2 Water bath temperature (°C) Particle size (nm) Surface charge (mV) 0 623.0±18.1 -17.8±0.3 35 516.9±8.4 -29.7±3.9 70 381.9±2.6 -37.8±1.8 Characterization results of 1.5AA-NLC Figure 1The particle size distribution of the AA-NLC prepared in Example 5 is shown. The average particle size is 381.9±2.6nm and the surface Zeta potential is -37.8±1.8mV, indicating that the prepared NLC has good stability. The surface potential, i.e., the Zeta potential, can reflect the stability of the colloidal dispersion system. The larger the absolute value, the higher the stability of the system.
[0041] 2. Appearance Figure 2 The image shown is a transmission electron microscope (TEM) image of the AA-NLC prepared in Example 5, which shows that the particles are irregularly spherical.
[0042] 3. XRD microstructure analysis Powder X-ray diffraction (XRD) results are shown in Figure 3 , Figure 3 In the figures, A, B, and C represent the XRD patterns of asiatic acid (AA) monomer powder, blank NLC, and AA-NLC prepared in Example 5, respectively. The AA monomer powder exhibits a sharp diffraction peak in the 2θ region of 10.7–17.0°, indicating that it is a crystalline drug. When AA is prepared into AA-NLC, a small and blunt peak appears at 2θ of 14.9°, indicating a decrease in drug crystallinity. The blank NLC shows no peak at this position (2θ of 14.9°), and the other peaks are roughly the same, suggesting that the drug is mostly dispersed in the carrier in molecular or amorphous form.
[0043] 4. Encapsulation efficiency and drug loading The encapsulation efficiency of the AA-NLC prepared in Example 5 was determined to be 77.9±4.8%, and the drug loading was 8.8±0.7%.
[0044] 5. In vitro release test Dialysis bags do not block or adsorb AA. The results of liquid concentration measurements inside and outside the dialysis bag showed that the dialysis bag had no blocking or adsorption effect on AA, and drug molecules could only enter and exit the dialysis membrane.
[0045] The in vitro release curves of AA-NLC are shown in the figure. Figure 4 The drug release exhibited a certain sustained-release characteristic, with a cumulative release of 85% over 5 days. At the same time, the residual drug nanoparticles in the dialysis bag were measured, and approximately 15% of the drug remained unreleased.
[0046] The above experimental results prove that: 1. In the solvent diffusion method, the aqueous phase does not contain surfactants. When a hot ethanol solution containing glyceryl monostearate, oleic acid and asiatic acid is added to the aqueous phase at the same temperature, the organic solvent that is easily miscible with water diffuses into the water, causing the solubility of lipids and drugs in the organic solvent to decrease rapidly. They precipitate out simultaneously in the form of a mixture to form NLC. The presence of liquid lipids prevents solid lipids from forming a more regular crystal lattice, which is beneficial for encapsulating drugs.
[0047] 2. The encapsulation efficiency of AA-NLC at the same concentration is 1.29 times that of AA. AA-NLC is dispersed in the form of nanoparticles, and AA exists in an amorphous form in the nanoparticles, suggesting that AA-NLC has higher bioavailability.
[0048] II. Preparation and Characterization of Microneedles The experimental animals were BALB / c mice, 4-6 weeks old, provided by the Experimental Animal Center of Zhejiang Academy of Medical Sciences. All experimental animals were treated with minimally painful methods (cervical dislocation). The experimental methods and purposes of the animals complied with human ethical standards and international practices.
[0049] 1. Research on the preparation process of lyophilized soluble microneedles (1) Preparation of PDMS microneedle negative mold Microneedle negative molds were prepared using a casting method. The negative mold material was polydimethylsiloxane (PDMS), which is very easy to demold and not easily deformed after reacting with the curing agent upon heating. The specific process is as follows: First, PDMS and curing agent were thoroughly mixed and poured into a six-well plate. Air bubbles generated during mixing were removed using a vacuum dryer. Then, metal microneedles were fixed in the center of the plate container, and the immersion depth of the metal microneedles was controlled. Next, it was placed in a 60°C drying oven for 8 hours to allow the PDMS to fully solidify. Finally, the metal positive mold was separated to obtain the desired microneedle negative mold. The specifications of the metal positive mold were: needle height 800 μm, 100 needles in total, and area 1 cm².
[0050] (2) Screening of microneedle matrix materials The matrix material and deionized water were mixed in the following weight ratio to prepare a gel: Chitosan (CS) gel: 10%, 20%, 30% (w / v); Polyvinylpyrrolidone (PVP) gel: 10%, 20%, 30%, 40% (w / v); Chondroitin sulfate sodium gel: 10%, 20%, 30%, 40% (w / v); Sodium carboxymethyl cellulose (CMC) gel: 10%, 20%, 30% (w / v); 100 μL of the prepared gel was placed in a six-well plate and placed in a constant temperature and humidity shaking chamber for 24 h. After that, it was freeze-dried and dried at room temperature and pressure to examine its comprehensive physical properties. It was used for the preliminary screening of microneedle matrix materials. The results are shown in Table 3.
[0051] Table 3 As shown in Table 3, among the single matrices of different concentrations, 30% CS, 40% sodium chondroitin sulfate, and 30% CMC showed better mechanical strength after freeze-drying, so they were further prepared into microneedles.
[0052] (3) Preparation of soluble microneedles by freeze-drying The gelled microneedle tip material was spread into the prepared microneedle negative mold (placed in a six-well plate) and placed in a vacuum drying oven. Under negative pressure, the cavity of the microneedle negative mold was filled. Finally, the microneedles were pre-frozen in a refrigerator and then freeze-dried in a freeze dryer. After drying, the complete microneedle patch was carefully removed with pointed tweezers. Microneedles were prepared using the above method with 30% CS, 40% sodium chondroitin sulfate, and 30% CMC. The performance evaluation results of microneedles obtained by casting with different matrices are shown in Table 4. It shows that the microneedles prepared with 30% CS, 40% sodium chondroitin sulfate, and 30% CMC all have good mechanical strength. However, 30% CS and 30% CMC have poor flowability and can only fill the cavity of the microneedle negative mold by centrifugation, and the morphology of the prepared microneedles is incomplete. The microneedles prepared with 40% sodium chondroitin sulfate have better overall physical properties. Therefore, sodium chondroitin sulfate was selected as the optimal microneedle matrix material for freeze-drying process research.
[0053] Table 4 matrix materials Liquidity Microneedle Formability Microneedle mechanical strength 30%CS Poor good excellent 40% chondroitin sulfate sodium better excellent excellent 30% CMC Difference good excellent 2. Characterization of lyophilized soluble microneedles (1) Mechanical property testing The mechanical properties of microneedles were investigated using the compression mode of a texture analyzer. When there are a large number of microneedles, it is difficult for them to simultaneously contact the test surface, making it challenging to observe the mechanical properties of each individual microneedle. Considering measurement error, the microneedles were cut into a 4×4 array and then fixed on the test platform. A P / 6 probe was selected as the sensing probe. The probe's downward speed was set to 0.5 mm / s, and the maximum compression distance was 0.8 mm. Before the test, the probe's height and pressure were calibrated. The microneedles were parallel to the probe's axis, with the tips pointing upwards. When the probe contacted the microneedle tip, the sensor recorded the applied pressure and transmitted it to the electronic information control system. Data recording automatically stopped after the maximum compression distance was reached.
[0054] To visually demonstrate the destructive effects of different forces on the mechanical properties of microneedles, polymer microneedles were placed face down on a smooth surface. Weights ranging from 0-200g (0-0.436N / needle) were applied to 4×4 array microneedles from the same batch, and the morphological changes of the microneedles under different stress conditions were recorded. The compression ratio of the microneedles was calculated by randomly selecting six needles and comparing their lengths before and after compression under different stresses.
[0055] (2) Morphological characterization of microneedles The morphology of the lyophilized microneedles was observed using field emission scanning electron microscopy (FE-SEM, HITACHI Regulus 8100) under high vacuum conditions with an accelerating voltage of 10 kV. Elemental distributions were analyzed using energy-dispersive X-ray spectroscopy (EDS, Oxford Ultim Max 65). The distribution and size of pores in the sample cross-section were observed using FESEM and analyzed using the NIH Image J program.
[0056] (3) Microneedle solubility test After drying, the microneedles were placed upside down on a pre-perforated polyethylene membrane, ensuring that only the tip was exposed to PBS buffer (pH 6.0, simulating skin pH). The membrane was then placed in a constant-temperature shaking incubator at 37°C and 50 rpm for a solubility experiment. At regular intervals, the microneedles were removed, their surface moisture was blotted dry with filter paper, and the solubility was observed and photographed under a microscope.
[0057] (4) Study on the skin penetration performance of microneedles For the experimental animals, healthy BALB / c mice were used as excised skin. After euthanizing the mice by cervical dislocation, the fur on the back and abdomen was immediately shaved off with a razor, and any remaining hair was removed with a fine razor. After hair removal, the skin from the back and abdomen was immediately harvested and laid flat on a clean surface. The subcutaneous fat and connective tissue were removed with cotton wool soaked in physiological saline, followed by rinsing with physiological saline. After drying with absorbent paper, the prepared lyophilized microneedles were inserted into the skin by pressing with the thumb and left in place for approximately 1 minute. The needle puncture marks left on the skin were observed. Since punctures cause death of nearby skin cells, trypan blue staining was used. Therefore, the puncture area was stained with 0.4 wt% trypan blue solution. Excess trypan blue was washed off after 5 minutes, and the puncture effect of the microneedles was observed. For histological sectioning, the inserted skin was fixed in 4 wt% paraformaldehyde, embedded in paraffin, and cut into 5 mm sections. Then, staining was performed using hematoxylin and eosin (H&E). To further visualize the insertion depth in the skin, lyophilized microneedles were inserted into isolated mouse skin, and 2D cross-sectional scans of the skin layer were performed using a self-modified optical coherence tomography (OCT) microscope to obtain real-time images of the insertion process. Finally, the obtained images were analyzed using ImageJ software to determine the insertion depth.
[0058] (5) Study on skin recovery performance after microneedle insertion To verify the low invasiveness of microneedling, the healing of the skin in mice after microneedle patch insertion was characterized over time. Mice were anesthetized with 5% (w / v) chloral hydrate, shaved, and microneedle patches were applied to the skin on the back of the mice. After 1 minute, the skin healing was photographed.
[0059] 3. Experimental Results and Discussion (1) Morphological characterization results of microneedles: The appearance and scanning electron microscope images of the microneedle patches prepared from 40% sodium chondroitin sulfate are shown in the figure. Figure 5 As shown, the microneedle array is neatly arranged, with each individual needle being conical in shape, having a smooth surface, and a sharp tip.
[0060] (2) Microneedle mechanical property test results: The test curve of the failure force of the microneedle tip prepared with 40% sodium chondroitin sulfate was obtained by texture analyzer, as shown in the figure. Figure 6As shown, initially, the microneedles undergo elastic deformation as the probe moves downwards. The initial part of the curve conforms to Hooke's Law, indicating that stress and strain are proportional. With increasing compressive displacement, two plateau phases are observed in the graph. The first plateau occurs when the microneedle tip undergoes buckling deformation, with a buckling force of 0.019 N / needle, consistent with the experimentally measured deformation at a compressive force of 0.013 N. The second plateau occurs when the microneedle tip fails and fractures, revealing a decrease in force. The maximum force applied before this decrease represents the mechanical strength or fracture force of the microneedle. The failure force of the lyophilized soluble microneedles is 0.0687 N / needle, indicating that the microneedles possess sufficient mechanical strength to pierce the skin and achieve drug delivery.
[0061] A force of 0-0.436 N was applied perpendicularly to microneedles prepared from 40% sodium chondroitin sulfate. The morphological changes and compressibility of the microneedles under different forces were as follows: Figure 7 As shown. Failure refers to the buckling and bending deformation of the microneedle under axial force. When a single microneedle is subjected to a force of 0.006 N (greater than the force required to penetrate the skin, 3.596 × 10⁻⁶ N), failure occurs. -4 The microneedle tip remained intact, showing no significant deformation or bending. Under a vertical force of 0.013 N, the microneedle began to bend and deform. When a vertical force of 0.125 N was applied to a single needle, the tip of the microneedle bent slightly, but without breakage, and the compressive force was less than 15%. This deformation test was conducted on a hard surface, which exaggerates the deformation of the microneedle compared to testing in soft tissue. Therefore, the chondroitin sulfate lyophilized soluble microneedles possess sufficient mechanical strength to penetrate the skin.
[0062] (3) Results of microneedle solubility experiment To verify the dissolution properties of microneedles prepared from 40% chondroitin sulfate sodium, the microneedles were inverted on a perforated PE membrane, exposing the needle tips to PBS buffer. The resulting dissolution diagram is shown below. Figure 8 As shown, over time, the microneedle tips gradually swell and dissolve, eventually dissolving completely. After 10 seconds, the very tip begins to dissolve; after 40 seconds, two-thirds of the microneedle is dissolved; and after 90 seconds, it is almost completely dissolved. This demonstrates that the prepared microneedles have excellent dissolving properties, thus allowing them to dissolve and release the loaded drug in the interstitial fluid when inserted into the skin.
[0063] (4) Results of microneedle skin penetration experiment To demonstrate that microneedles can penetrate the stratum corneum and enter intradermal tissue, a 0.4% trypan blue solution was used to stain the microneedle array area. Healthy cells repel trypan blue, while dead cells, due to loss of membrane integrity and increased permeability, can be stained blue by trypan blue. After the microneedles pierce the stratum corneum, living cells within the epidermis can be stained. Figure 9 As shown, the microneedle patch exhibits a neat and clear array of pinholes on the skin surface. These pinholes are clearly visible after trypan blue staining, with a penetration rate exceeding 90%. This indicates that the freeze-dried microneedle patch possesses sufficient mechanical strength to penetrate the skin.
[0064] (5) Evaluation of the skin recovery performance of microneedles A microneedle patch was placed on the skin for a skin puncture test. The patch was pressed for 1 minute, then removed. The recovery process was observed and photographed. Figure 10 As shown in the image, when the microneedle patch was first removed, the indentation and micropores were faintly visible, and the color was light. Over time, redness appeared at the needle tips, gradually deepening in color, reaching its peak at 12 minutes. The redness then gradually faded, and the skin fully recovered at 28 minutes. This indicates that the freeze-dried microneedles have minimal skin irritation and high safety.
[0065] This invention also combines asiatic acid nanostructured lipid carriers with a microneedle transdermal delivery system to construct a nano-microneedle dual-carrier system for treating skin scar tissue. First, various polymer materials were screened, and the optimal microneedle matrix material suitable for scars was found by changing the material composition and molecular weight. Finite element simulation combined with material testing and evaluation, transdermal experiments, etc., were used to select soluble microneedles that could easily penetrate the stratum corneum into the skin, dissolve rapidly, allow for rapid separation of the needle tip and backing, and have a certain degree of viscosity. The axial force, lateral force, and friction generated during microneedle insertion into scar tissue, as well as the interaction between the microneedles and the skin during insertion, were analyzed, laying the foundation for the precise manufacturing of the dual-carrier system.
[0066] In subsequent processes, asiatic acid nanostructured lipid carrier powder was loaded into the needle tip and patch to construct a novel transdermal delivery method based on microneedle nanostructured lipid carrier. By combining microneedles and nanostructured lipid carrier, the transdermal absorption of poorly soluble Chinese medicine components can be promoted, giving full play to the physicochemical permeation-enhancing advantages of microneedle-nanostructured lipid carrier, increasing transdermal penetration, and utilizing the sustained-release properties of nanostructured lipid carrier to reduce adverse drug reactions, thereby achieving the effect of synergistic effect and reduced toxicity, and maximizing the efficacy of asiatic acid.
[0067] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A preparation process for a asiatic acid nanostructured lipid carrier, characterized in that, Includes the following steps: S1. Weigh 4-6 parts by weight of asiatic acid, 34-38 parts by weight of solid lipids, and 7-10 parts by weight of liquid lipids, and dissolve them in 4-6 mL of anhydrous ethanol. S2. At 65-75℃, add the above mixed solution to 50mL of water at the same temperature and stir until homogeneous to obtain a cloudy liquid with an opalescent appearance. S3. After cooling the turbid liquid to room temperature, adjust the pH with hydrochloric acid. The precipitate obtained by centrifugation is washed with a small amount of deionized water, centrifuged again, and the upper liquid is discarded to obtain the asiatic acid nanostructure lipid carrier precipitate. S4. The asiatic acid nanostructured lipid carrier precipitate was freeze-dried to obtain asiatic acid nanostructured lipid carrier freeze-dried powder.
2. The preparation process of the asiatic acid nanostructured lipid carrier according to claim 1, characterized in that, In step S1, the solid lipid is glyceryl monostearate and the liquid lipid is oleic acid.
3. The preparation process of the asiatic acid nanostructured lipid carrier according to claim 2, characterized in that, In step S1, the amount of asiatic acid used is 5 parts by weight, the amount of solid lipid used is 36 parts by weight, the amount of liquid lipid used is 9 parts by weight, and the amount of anhydrous ethanol used is 5 mL.
4. The preparation process of the asiatic acid nanostructured lipid carrier according to claim 3, characterized in that, In step S2, the heating temperature of the mixed solution is 70°C.
5. A asiatic acid nanostructured lipid carrier, characterized in that, It is prepared by any one of the preparation processes described in claims 1-4.
6. The application of the asiatic acid nanostructured lipid carrier as described in claim 5, characterized in that, The asiatic acid nanostructured lipid carrier is used as a drug for treating scar tissue.
7. A soluble microneedle drug delivery system, characterized in that, The soluble microneedle drug delivery system is a microneedle patch, which consists of a microneedle tip and a patch, and the asiatic acid nanostructure lipid carrier described in claim 5 is loaded into the microneedle tip and / or the patch.
8. The soluble microneedle drug delivery system according to claim 7, characterized in that, The matrix material of the microneedle patch is sodium chondroitin sulfate.
9. The soluble microneedle drug delivery system according to claim 8, characterized in that, The chondroitin sulfate sodium mass fraction is 35-45%.
10. The soluble microneedle drug delivery system according to claim 9, characterized in that, The chondroitin sulfate sodium gel material was spread into the prepared microneedle negative mold and placed in a vacuum drying oven. Under negative pressure, the chondroitin sulfate sodium gel material filled the cavities of the microneedle negative mold. The microneedle mold was then placed in a refrigerator for pre-freezing and subsequently placed in a freeze dryer for freeze drying. After drying, the complete microneedle patch was picked up with pointed tweezers.
Citation Information
Patent Citations
Asiatic acid lipid nanoparticle capable of stimulating oral absorption and preparation method thereof
CN103040791A
Madecassic acid solid lipid nanoparticle gel
CN111920760A
Porous structure soluble microneedle based on freeze drying technology and preparation method and application thereof
CN115737606A
Scar-removing microneedle patch containing centella asiatica active ingredient
CN116869848A
Preparation and application of AS-PNS nanocrystal loaded soluble microneedle for scar repair
CN118415958A